2020
DOI: 10.1080/14631369.2020.1776097
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the asymmetries? African students’ mobility to China

Abstract: African students' mobility to China is growing-making China the second most popular destination for African students studying abroad, after France. Generally, due to the pervasive poverty and inequality in African states, educational mobility is a means to escape individual socioeconomic challenges for the transformation of lives. However, is the African students' mobility to China able to achieve those expectations? Through a critical analysis of current scholarship in African student education mobility the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Nordtveit (2011) attributed what he perceives as the biased recruitment process to China's non-interference principle, which authorizes recipient countries to control the selection of participants. Hodzi (2020) mentioned widespread corruption, with scholarships and training opportunities being awarded to children of the ruling elites, that reproduce social inequalities in aid recipient countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nordtveit (2011) attributed what he perceives as the biased recruitment process to China's non-interference principle, which authorizes recipient countries to control the selection of participants. Hodzi (2020) mentioned widespread corruption, with scholarships and training opportunities being awarded to children of the ruling elites, that reproduce social inequalities in aid recipient countries.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have concluded that China's educational aid programs enhance international students' positive impressions of China and thus increase China's soft power (Benabdallah, 2019; Chan and Wu, 2020; Dong and Chapman, 2008; Ham and Tolentino, 2018; Haugen, 2013; Hodzi, 2020; Latief and Lefen, 2018; Makundi et al. , 2017; Mulvey, 2020; Nitza-Makowska, 2022; Tugendhat and Alemu, 2016; Yuan, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each sees the mobility to China as an opportunity to an end. Commonly, mobility to China is a modus operandi to escape the unfavorable socioeconomic conditions at home (Hodzi, 2020) and a path to a prosperous future (Brown, 2012). In this respect, financial support, ease of visa access and hopes for better education provide the right incentives for mobility (Gbollie and Gong, 2020).…”
Section: On African Students In Chinamentioning
confidence: 99%